Peran Mediasi Citra Merek pada Inovasi Produk dan Relationship Marketing terhadap Loyalitas Pelanggan di Restoran X Surabaya - Kusuma, Celine Patricia; Limorita, Clarissa; Moses Soediro; Leoparjo, Fabiola (ITB AAS Indonesia Surakarta, 2025)
The research examines how product innovation and relationship marketing influence customer loyalty at Restaurant X in Surabaya, where brand image serves as a mediating variable. A quantitative research technique was applied by collecting data through a survey which involved 120 participants selected by a purposive sampling. Data was gathered through an online questionnaire utilizing a Likert Scale from 1 to 4. The data were processed using SmartPLS. The results of this study show that, 1)Product Innovation positively influences Brand Image, 2) Relationship Marketing positively influences Brand Image, 3) Brand Image positively influences Customer Loyalty, 4) Product Innovation positively influences Customer Loyalty through Brand Image, 5) Relationship Marketing positively influences Customer Loyalty through Brand Image.